Robust Design Optimization of Electromagnetic Actuators for Renewable Energy Systems Considering the Manufacturing Cost - Jie Deng (Energies, 2019)
Power transmission and protection of power electronics−electromagnetic actuators are crucial parts in renewable energy systems (energy management of photovoltaic, wind power, hybrid and electric vehicles). Consistency optimization of electromagnetic actuators has attracted extensive attention from corporations in competitive markets. Robust design has been widely applied for reducing the influence of uncertainties in the manufacturing process to improve the consistency of product quality. However, the cost factors of the actual manufacturing process are not fully considered in state-of-art methods. Although the consistency has been improved, the optimization scheme may not be optimal from the perspective of engineering applications, because unnecessary cost increments may be produced. In this paper, an application-oriented robust design method for consistency optimization is proposed. The impact of tolerance values on quality loss and manufacturing cost can be considered simultaneously to guide the tolerance optimization process. Thus, the optimal solution of total loss is obtained by optimizing the quality fluctuation to the design objective with the minimum increment of manufacturing cost. An example of the consistency optimization of an electromagnetic actuator used in the photovoltaic system is presented to illustrate the procedure and verify the effectiveness of the proposed method.